Cell functions in Drosophila oogenesis. - Malva, C.; Graziani, F.; Gargiulo, G.; Manzi, A. (Genetica, 1994)
We are studying Drosophila oogenesis by analysing at genetic and molecular levels several female-sterile mutations. Some (hold up, wavoid-like and abnormal oocyte) have been isolated by L. Sandler in region 32 of the second chromosome; others have been isolated by us and their phenotype is presented for the first time in this paper. We performed chromosome walking in 32D-32E-F(250 Kb) and 32A-B(100 Kb) and in the last years we molecularly identified several genes with specific maternal expression patterns. We will review here our studies on two of these genes: the Vitelline Membrane Protein gene 32E and the gene coding for a receptor form of Guanylate Cyclase.